2017
DOI: 10.1016/s2352-3026(16)30194-6
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib for symptom control in patients with chronic lymphocytic leukaemia: a single-group, phase 2 trial

Abstract: Summary Background Disease-related symptoms impair the quality of life of countless patients with chronic lymphocytic leukemia (CLL) who do not require systemic therapy. Currently available therapies are not specifically aimed at symptom control. Because stimulation of the B-cell receptor activates Janus kinase (JAK)-2 in CLL cells and the JAK2 inhibitor ruxolitinib improves symptoms of patients with myelofibrosis, we hypothesized that ruxolitinib would improve disease-related symptoms in CLL patients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…While the first trial reported a decrease of lymph node size in almost 50% of patients, the study was stopped early due to a high incidence of severe anemia [47]. The second trial showed that ruxolitinib significantly improved disease-related symptoms, decreased serum cytokines, and caused leukemic cell mobilization from lymphoid organs [48]. These trials provide preliminary observation of the positive effect of JAK2/STAT3 targeting in CLL, either alone or in combination with BTK inhibitors.…”
Section: Discussionmentioning
confidence: 94%
“…While the first trial reported a decrease of lymph node size in almost 50% of patients, the study was stopped early due to a high incidence of severe anemia [47]. The second trial showed that ruxolitinib significantly improved disease-related symptoms, decreased serum cytokines, and caused leukemic cell mobilization from lymphoid organs [48]. These trials provide preliminary observation of the positive effect of JAK2/STAT3 targeting in CLL, either alone or in combination with BTK inhibitors.…”
Section: Discussionmentioning
confidence: 94%
“…Anderson symptom inventory (MDASI) and the Functional Assessment of Anorexia Cachexia Therapy (FAACT) scale, to assess their symptom burden and quality of life. The MDASI has been validated and is a frequently used questionnaire for assessing symptom . We used the MDASI to assess the symptom burden of our patients.…”
Section: Methodsmentioning
confidence: 99%
“…Here it could be shown that anti-IgM mediated BCR stimulation induces STAT3 activation signaling in CLL (42). In a clinical trial inhibition of JAK2 by ruxolitinib decreases symptoms (43), however therapeutic impact regarding relevant endpoints such as PFS and OS remains to be clarified. Finally, Kondo et al could show that ibrutinib treatment of CLL cells also inhibits STAT3 phosphorylation and described suppression of IL10 and PD-L1 in ibrutinib treated CLL patient cells (44).…”
Section: Discussionmentioning
confidence: 98%